2009
DOI: 10.1007/s00595-009-3988-7
|View full text |Cite
|
Sign up to set email alerts
|

Pouchitis disease activity index (PDAI) does not predict patients with symptoms of pouchitis who will respond to antibiotics

Abstract: Antibiotic treatment was effective in a considerable number of ulcerative colitis patients whose PDAI score was less than 7 after IPAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Patients with pouchitis currently experience a series of complications, and the diagnosis of pouchitis remains challenging . At present, the mPDAI is recommended as a widely accepted tool for detecting this severe complication after IPAA, even though there are considerable issues with this diagnostic tool . However, for the purpose detection, it has become increasingly necessary to find a simpler and better indicator of pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with pouchitis currently experience a series of complications, and the diagnosis of pouchitis remains challenging . At present, the mPDAI is recommended as a widely accepted tool for detecting this severe complication after IPAA, even though there are considerable issues with this diagnostic tool . However, for the purpose detection, it has become increasingly necessary to find a simpler and better indicator of pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some authors claim that biopsy taking and pathologic evaluation is unnecessary due to economic reasons. Moreover, to simplify classification, the proposed Japanese criteria of pouchitis does not contain any pathology findings or scoring system [11]. However, even if the detailed description of acute inflammation was redundant for some [17], and not a good indicator of clinical outcome, Kohyama et al proved that patients with low PDAI had better response to antibiotic treatment [11].…”
Section: Methodsmentioning
confidence: 99%
“…The index was introduced by Sandborn et al in 1994; it consists of clinical, endoscopic and histological sections, and allows for the diagnosis of pouchitis when total score equals 7 or higher [10]. However, some publications suggest the possibility of inflammation with scores below 7, which raised some criticism [11]; nevertheless, PDAI remains one of the most important and accepted tools for diagnosing pouchitis [12]. This scale is primarily based on subjective patient symptoms and subjective assessment by the examining physician.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve of the 59 studies reported on patients with FAP and demonstrated a pooled prevalence of 0.06 (95% CI 0.03-0.15) with an insignificant heterogeneity (I 2 = 77%, P < 0.01) (Figure 3). The Egger's Barnes 2020 [11] Barnes, Herfarth 2020 [22] Ferrante 2008 [30] Fleshner 2007 [8] Gorrepati 2018 [32] Hashimoto 2014 [33] Heuschen 1999 [10] Ikeuchi 2004 [17] Kohyama 2009 [41] Kostrejova 2015 [42] Okita 2021 [55] Sengul 2006 [59] Stahlberg 1996 [61] Suzuki 2012 [9] Teixeira 2003 [63] Villamil 2011 [67] White 2010 [12] Yamamoto-Furusho 2015 [70] Random effects model…”
Section: Familialadenomatouspolyposismentioning
confidence: 99%
“…Twenty-five studies reported on chronic pouchitis in UC with a pooled prevalence of 0.13 (95% CI 0.10-0.18) and a significant heterogeneity (I 2 = 94%, P < 0.01) (Figure 6). Egger's test indicated funnel plot Barnes 2020 [11] Barnes, Herfarth 2020 [22] Carcamo 2020 [24] Fazio 2013 [29] Ferrante 2008 [30] Fleshner 2007 [8] Gorrepati 2018 [32] Hashimoto 2014 [33] Heuschen 1999 [10] Hoda 2008 [34] Ikeuchi 2004 [17] Kohyama 2009 [41] Kostrejova 2015 [42] Mowschenson 2000 [52] Okita 2021 [55] Sengul 2006 [59] Stahlberg 1996 [61] Suzuki 2012 [9] Teixeira Sensitivity analysis was carried out by removing those studies reporting on acute pouchitis that fell outside of the funnel plot and thus may account for publication bias. A forest plot (Figure 7) of the remaining studies demonstrated a pooled prevalence of 0.18 (95% CI 0.15-0.20) without significant heterogeneity (I 2 = 49%, P = 0.01).…”
Section: Acuteandchronicpouchitisinucmentioning
confidence: 99%